2020
DOI: 10.29219/fnr.v64.4456
|View full text |Cite
|
Sign up to set email alerts
|

Association between parental feeding practices and shared family meals. The Food4toddlers study

Abstract: Background: Parental feeding practices and family meals are important determinants for infants' diet and health. Still, there is no previous research of the association between feeding practices and family meals in infants. Objective: Explore potential associations between feeding practices and family meals among infants. Design: We present cross-sectional results (baseline) from the Food4toddlers study. In total 298 parents of 1-year-olds, recruited from all over Norway, filled in a questionnaire regarding fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…For frequency of family meals and use of nonrecommended child feeding practices, the associations were moderate to strong. As an extension of these findings, a previous paper from our research group reported that having family meals every day was associated with positive parental feeding practices, while having family meals less often was associated with negative feeding practises (Øverby et al, 2020 ). Taken together, these findings indicate that maternal symptoms of anxiety and depression may have implications for both the quantity and the relational feeding quality of the family meal.…”
Section: Discussionsupporting
confidence: 58%
“…For frequency of family meals and use of nonrecommended child feeding practices, the associations were moderate to strong. As an extension of these findings, a previous paper from our research group reported that having family meals every day was associated with positive parental feeding practices, while having family meals less often was associated with negative feeding practises (Øverby et al, 2020 ). Taken together, these findings indicate that maternal symptoms of anxiety and depression may have implications for both the quantity and the relational feeding quality of the family meal.…”
Section: Discussionsupporting
confidence: 58%
“…The same study found that non‐technology object‐related distractions and fathers' total distractions were negatively associated with maternal feeding response 42 . Baseline data from the Norwegian Food4toddlers study revealed that not eating family meals together was a barrier which enacted negative practices such as pressure to eat and restriction 64 …”
Section: Resultsmentioning
confidence: 92%
“…The majority of studies were conducted in the USA ( n = 20), 24–43 followed by Australia ( n = 10), 44–53 United Kingdom ( n = 8), 54–61 New Zealand ( n = 1), 62 Norway ( n = 2), 63,64 and Sweden ( n = 1) 65 . Thirty‐four studies, reported in 33 papers, employed a quantitative design, including RCTs of an intervention ( n = 5), 32,39,50,62,63 observational cohort studies ( n = 8), 24,27–29,35,54,59,60 cross‐sectional studies ( n = 11), 24,30,38,41–44,46,48,53,64 a case–control study, 26 a within‐subject experimental study, 40 a quasi‐experimental study, 51 and observational descriptive/measurement development 31 . Six studies undertook secondary analyses; two used cross‐sectional data, 25,37 two studies used data from observational cohort studies, 33,45 one used control group data, 34 and one used data from an RCT 36 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the studies are limited to toddlers <1 years, and to the intake of fruits and vegetables ( 20 22 ). Moreover, some studies conducted in Norway have explored feeding practices in relation to other endpoints than food intake, like shared family meals ( 21 , 22 ). The main aim of this study was to explore the possible association between parental feeding practices and the intake of vegetables, fruits/berries, fish, foods with added sugars, and SSB in Norwegian preschoolers.…”
Section: Popular Scientific Summarymentioning
confidence: 99%